Futures Prices in Supply Analysis: Are Instrumental Variables Necessary? - Hendricks, Nathan P.; Janzen, Joseph P.; Smith, Aaron (My University, 2014)
Crop yield shocks are partially predictable—high planting-time futures prices have tended to indicate that yield would be below trend. As a result, regressions of total caloric production on futures prices produce estimates of the supply elasticity that are biased downwards by up to 75%. Regressions of the world’s growing area on futures prices have a much smaller bias of about 20% because although yield shocks are partially predictable, this predictability has a relatively small effect on land allocation. We argue that the preferred method for estimating the crop supply elasticity is to use regressions of growing area on futures prices and to include the realized yield shock as a control variable. An alternative method for bias reduction is to use instrumental variables (IVs). We show that the marginal contribution of an IV to bias reduction is small—IVs are not necessary for futures prices in supply analysis.
Citation: Nathan P. Hendricks, Joseph P. Janzen, Aaron Smith; Futures Prices in Supply Analysis: Are Instrumental Variables Necessary?, American Journal of Agricultural Economics, Volume 97, Issue 1, 1 January 2015, Pages 22–39, https://doi.org/10.1093/ajae/aau062
Keywords: JEL: Q11 - Aggregate Supply and Demand Analysis; Prices